Efektivitas Model Guided Discovery Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Ikatan Kimia - Irfandi (Unika Santu Paulus Ruteng, 2023)
The guided discovery model is effective for improving student learning outcomes on chemical bonding material in Class X TKJ SMK Bina Profesi Pekanbaru. This type of research used pre-experiment with one group pretest and posttest design. Sampling was carried out based on the considerations of 2 class X TKJ obtained class X TKJ 1. The data analysis technique used was paired t-test. Based on the results of the data analysis test, it was obtained that tcount>ttable was 92.85%, meaning that the use of the Guided Discovery strategy could improve student learning outcomes on chemical bonding material in Class X TKJ SMK Bina Profesi Pekanbaru